FLEKSIBILITAS HAK DAN KEWAJIBAN SUAMI ISTRI PERSPEKTIF MUBADALAH - Afif Sabil Afif; Ach. Zukin Zukin (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2024)
One of the consequences of marriage is the existence of rights and obligations for husband and wife. So far, these rights and obligations have been understood statically, the husband is obliged to earn a living while the wife's obligation is to serve her husband, look after the house and all other domestic duties. Is that true? Couldn't it be if the rights and obligations of husband and wife were understood dynamically? These questions then led researchers to conduct research with the title Flexibility of the Rights and Obligations of Husbands and Wives from Mubadalah perspective. By using a qualitative research approach, this type of literature study, this research concludes that rights and obligations in the household are a dynamic matter, where husband and wife can work together to earn a living, manage finances together and help each other carry out domestic work. Adapted to situations and conditions and based on the concept of mu'asyarah bi al-ma'ruf.